2013
DOI: 10.3758/s13428-013-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the psycholinguistic variables on the lexical decision task in Spanish: A study with 2,765 words

Abstract: In order to explore the role of the main psycholinguistic variables on visual word recognition, several mega-studies have been conducted in English in recent years. Nevertheless, because the effects of these variables depend on the regularity of the orthographic system, studies must also be done in other languages with different characteristics. The goal of this work was to conduct a lexical decision study in Spanish, a language with a shallow orthography and a high number of words. The influence of psycholing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
3
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 28 publications
2
44
3
2
Order By: Relevance
“…On the other hand, the lexical route might not be necessary in transparent languages (that is, with transparent orthography, such as German or Spanish; Frost & Katz, 1992), since words can be read using only grapheme-phoneme conversion rules (i.e., via the nonlexical route). However, researchers have found the presence of lexical effects (e.g., frequency, neighbourhood), in German (Ziegler, Perry, & Coltheart, 2000) or in Spanish (González-Nosti, Barbón, Rodríguez-Ferreiro, & Cuetos, 2014;Martín Plasencia, Iglesias Dorado, & Serrano, 2008) in reading aloud as well as in lexical decision tasks, which evidenced the use of the lexical route in transparent languages too.…”
Section: Visual Word Recognition Modelsmentioning
confidence: 99%
“…On the other hand, the lexical route might not be necessary in transparent languages (that is, with transparent orthography, such as German or Spanish; Frost & Katz, 1992), since words can be read using only grapheme-phoneme conversion rules (i.e., via the nonlexical route). However, researchers have found the presence of lexical effects (e.g., frequency, neighbourhood), in German (Ziegler, Perry, & Coltheart, 2000) or in Spanish (González-Nosti, Barbón, Rodríguez-Ferreiro, & Cuetos, 2014;Martín Plasencia, Iglesias Dorado, & Serrano, 2008) in reading aloud as well as in lexical decision tasks, which evidenced the use of the lexical route in transparent languages too.…”
Section: Visual Word Recognition Modelsmentioning
confidence: 99%
“…It should be noted, however, that a number of lexical and sublexical variables influence word processing, such as frequency, age of acquisition, the number of orthographic neighbors (González-Nosti, Barbón, Rodríguez-Ferreiro, & Cuetos, 2014), syllable frequency (Carreiras, Alvarez, & De Vega, 1993), and the number of letters or syllables (Acha & Perea, 2008). In addition, word recognition is affected by semantic dimensions such as concreteness, imageability, number of associates, and semantic ambiguity (see Pexman, 2012, for an overview).…”
mentioning
confidence: 99%
“…Interestingly, two studies published on languages with consistent spelling systems, Spanish and Dutch, have found no effects of imageability on lexical decision times and ERPs (Alija & Cuetos, 2006;Brysbaert, Lange, & Van Wijnendaele, 2000;Cuetos, Barbón, Urrutia, & Dominguez, A., 2009). These findings are, however, problematic since other studies have shown an effect of imageability in lexical decision times and ERPs in transparent languages such as Spanish (Dominguez, de Vega & Cuetos, 1997;González-Nosti, Barbón, Rodríguez-Ferreiro & Cuetos, 2014;Wilson, Cuetos, Davies, & Burani, 2013). In addition inferring from a lack of imageability effect that there is no semantic involvement in the recognition of words in transparent languages might seem as an excessive assumption, in particular because imageability is not the only factor that reveals properties of the semantic system.…”
mentioning
confidence: 58%